Detection and Warning System for Motorcycle Vehicular Collision Avoidance - Abdul Rashid, M.A.; Yahya, W.J.; Ithnin, A.M.; Zamzuri, H.; Ken, T.L.; Ryunosuke, S.; Dwijotomo, A.; Abu Kassim, K.A.; Ahmad, Y.; Md Isa, M.H.; Mohd Jawi, Z. (Journal of the Society of Automotive Engineers Malaysia, 2021)
World Health Organisation has determined that South-East Asian region has the highest road traffic death in 2015 involving motorised 2-3 wheelers. Generally, motorcycles are lack of active safety features that capable to prevent road accident. Therefore, this study aims to design and develop active safety features for a motorcycle to prevent a frontal collision through an audible warning to the motorcyclist and detected object when the collision is about to happen. The system should consist of a simple algorithm with a minimum set of hardware. Based on the design criteria for the system, an audible warning will only be given when all three conditions stated below are met. (1) An object is within stopping distance limit, (2) object heading towards the centre of motorcycle and (3) relative velocity of an object might cause a frontal accident. The system called Detection and Warning System for Motorcycle Vehicular Collision Avoidance (DEWAMCA). It is expected that DEWAMCA can assist currently available Blind Spot Detection System (BSDS) to reduce accident involving motorcycles significantly.